POTENSI ABU DARI TULANG IKAN TONGKOL SEBAGAI ADSORBEN ION MANGAN DALAM LARUTAN - Puji Astuti; Sofia Anita; Tengku Abu Hanifah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Tuna fish bone waste has not been used optimally yet. The tuna bone contains phosphate calcium and carbonate calcium so that oxide calcium can be formed when they are calcinated. Oxide calcium pattern which is relatively opened is hexagonal in shape, inside the shape H+ and other ions are trapped hence it is potential to be an adsorbent. This study was conducted to determine the absorption ability of oxide calcium based on various concentrations and contact times. Manganese analysis was performed using Atomic Absorption Spectroscopy (AAS). The highest absorption ability of oxide calcium to manganese based on variation of concentrations (10 mg/L, 30 mg/L dan 50 mg/L) was 60.334% for 50 mg/L of manganese concentration and immerse time of 20 hours with 5, 10, 15, 20, and 24 hours contact time. Optimum asorption was found at 20 hours of immerse time and 50 mg/L of manganese concentration analyzed with a value of 98.19%. Level of calcium and oxide calcium in ash of tuna bones analyzed by complexometry were 22.44% and 31.36%, respectively.